Upaya guru dalam menyusun materi bahasa arab berbasis pendekatan komunikatif - Sa'diyah, Lu'lu'atun Nadhirotus (Maliki Interdisciplinary Journal, 2025)
This article aims to examine the role and strategies of teachers in developing Arabic language learning materials based on a communicative approach. This approach emphasizes the use of language as a contextual and meaningful communication tool, rather than merely mastering grammatical structures. Through a literature review, this article reveals that teachers have a strategic position as learning designers who understand the needs, characteristics, and backgrounds of students. The materials are developed by selecting contextual themes, composing dialogues (hiwār), designing communicative assignments, and integrating visual media. The results of the study show that these strategies are effective in improving students' language skills, particularly in speaking and comprehension. Institutional support, such as training and collaboration spaces, is needed so that teachers can develop materials in a sustainable manner that is responsive to students' needs.